Yamang ganda an organic cosmetics resource and entrepreneurship hub - Virtucio, Patricia Grace L. (College of Architecture, University of the Philippines Diliman, 2019)
The organic cosmetics industry in the Philippines is one with much untapped potential. With the country being as rich as it is in natural and human resources, and the wealth of information available to the public, the industry has welcomed a significant number of micro, small and medium industries. Despite this, these small businesses struggle with their operations, due to their disconnect to critical resources and services. To answer these issues, the design approach aimed to integrate services, spaces and users into one development, and introduce a newer, more collaborative model of business operation to an ever-evolving, compatible industry. This was done through the placement of small-scale commercial spaces, a business incubator, shared research and resource spaces, and a shared manufacturing facility. The goal of the design is to be able to realize the potential of this industry, and to introduce it to the general public.